On the Polarization Characteristics of middle latitude Geomagnetic Micropulsations (MAUSAM, 1967)
Geomagnetic micropulsations of different types are observed on the Soviet stations in the middle latitudes of the Northern hemisphere, Behaviour of the 'horizontal disturbed vector is analysed. Micropulsations of Pc2-4 and Pi2 types are shown to have statistically dominant counter-clockwise sense of rotation in the morning hours but clockwise sense of rotation in the evening hours. Both the rotational character of polarization and the diurnal variation of the sense of rotation suggest the Alfven (transverse) hydromagnetic thanks to mode is an important part of the micropulsation mechanism, although it is difficult to explain the micopulsation occurrence in middle and low latitudes Ignoring the magneto-acoustic (longitudinal) mode of propagation. All the micropulsation types appear to have the preferred directions characteristic of the observational point Diurnal variation of the hourly mean directions are similar at different sites and appear to have the largest departure progress of from the mean around the morning and the evening hours. Directional properties of micropulsations can be explained by the lateral in-homogeneities in the sub-surface geo-electrical structure.